Tapeworms (Cestoda: Proteocephalidea) of Synodontis spp. (Siluriformes) in Africa: survey of species and their redescriptions - Chambrier, Alain De; Scholz, Tomáš; Mahmoud, Zuheir N.; Mariaux, Jean; Jirků, Miloslav (Zootaxa, 2011)
Proteocephalidean tapeworms parasitic in Synodontis spp. (Siluriformes: Mochokidae) in Africa are critically reviewed based on examination of their type specimens and extensive new material from Kenya and Sudan. Proteocephalus synodontis Woodland, 1925 and Proteocephalus membranacei Troncy, 1978 are considered to be valid and both species are redescribed. Proteocephalus synodontis differs from congeners parasitic in other African freshwater fishes, including P. membranacei, in the possession of an extraordinarily developed inner longitudinal musculature formed by massive bundles of muscle fibres. A considerable variability was found in the size (35–140 × 30–75 μm) and shape (from elongate, tear-shaped to spherical) of the apical organ, which was present in all specimens from the Nile River basin in the Sudan, but absent in all but two juvenile specimens from Lake Turkana in Kenya. A congruent low molecular variability was also observed and these slight morphological and genetic differences may indicate ongoing allopatric speciation of tapeworms from the two previously connected basins. Nevertheless, all tapeworms were identical in all other morphological and molecular characteristics and are considered conspecific. Proteocephalus largoproglottis Troncy, 1978 from Synodontis membranacea from Lake Chad is synonymized with P. membranacei described from the same host and locality. Proteocephalus synodontis and P. membranacei differ from each other in the development of the inner longitudinal musculature, shape of the scolex and presence of weakly developed, almost indistinguishable ventral osmoregulatory canals in the latter species.